miR-325-3p Regulates Epithelial-mesenchymal Transition, Invasion and Metastasis of Gastric Cancer via Targeting CLDN1 Gene - DU Jitao; CAO Jian; ZHAO Wen; WAN Xiangbin; LI Zhi (Zhongliu Fangzhi Yanjiu, 2021)
Objective To investigate the effects of miR-325-3p on the EMT, invasion and metastasis of gastric cancer cells by targeting CLDN1 gene. Methods We selected human gastric epithelial cell lines GES-1 and gastric cancer cell lines HGC27, SGC-7901, MKN-45 and MGC-803, and detected the expression of miR-325-3p and CLDN1. The targeting relation between miR-325-3p and CLDN1 were verified by dual luciferase report experiments, and the expression of miR-325-3p and CLDN1 in gastric cancer cells were intervened. qRT-PCR and Western blot were adopted to detect N-cadherin, vimentin and MMP2 expression in cells. CCK-8 assay, Transwell assay, flow cytometry were utilized to detect cell proliferation activity, invasion and apoptosis, respectively. Results Compared with GES-1 cells, miR-325-3p expression was decreased while CLDN1 expression was increased in MGC-803 cells (P < 0.05). CLDN1 was a target gene of miR-325-3p. Overexpression of miR-325-3p could inhibit the proliferation, invasion and EMT of gastric cancer cells, while promote the apoptosis of gastric cancer cells. However, the inhibition of miR-325-3p had the opposite effect (P < 0.05). The overexpression of CLDN1 could reverse the effect of miR-325-3p overexpression on the biological behavior of gastric cancer cells. Conclusion miR-325-3p can suppress CLDN1, inhibit the invasion, metastasis and EMT while promote the apoptosis of gastric cancer cells. miR-325-3p is expected to be a new target in gastric cancer treatment.